Determinisme Teknologi: Penggunaan ICT dalam Pembelajaran Daring - Clarissa Adeline; Irwansyah Irwansyah (Jurnal Nomosleca, 2022)
This  study  aims  to  see  how  technology  has determined our learning system through the use of ICT in online learning. The use of technology in the education sector brings a massive  transformation  in  our learning  system.  In  addition  to that, the emergence of Covid 19 has also changed the education system into  online  learning. This study  uses  a  qualitative approach and systematic literature  review approach. Data collection used are  observation  and  semi-structured  interview with  2  informants that actively involved  in  online  learning.  The validity  of this  research  use  source  triangulation.  The  result  of this study shows that the ICT is used in every stages of learning process, from preparation, delivery and evaluation stage. Online learning cannot be separated from the role of technology, and it is shown that technology has determined online learning process. Keywords: Technology Determinism, ICT, Online Learning